THE PERFORMANCE IMPROVEMENT OF OCBC NISP BANK'S TRADE OPERATIONS DIVISION EMPLOYEES : APPLICATION OF ANALYTIC NETWORK PROCESS METHODS - Andreas Murti (UNIVERSITAS PAKUAN, 2019)
This study discusses the system design for improving the performance of OCBC NISP Bank's Trade Operations division employees using the Analytic Network Process (ANP) method. Performance measurement and scope of analysis is carried out on the activities of employees of the Trade Operations section in the process of issuing LC documents. This research determines what policy strategies can help improve the performance of OCBC NISP Bank's Trade Operations employees. The results of the study using the ANP method show that by implementing a productivity-based compensation system is a top priority with a priority weight of 42.69%. Whereas work process improvement is the second priority with 36.72% priority weight. For the last priority, the sequence is the preparation of the right target and key performance indicator (KPI) with a priority weight of 20.57%. Based on the results of ANP analysis, implementing a productivity-based compensation system provides the highest benefits and opportunities compared to the risks that may arise. Productivity-based compensation will motivate employees to compete to increase productivity to get better compensation compared to employees with lower productivity.